2012
DOI: 10.1080/07448481.2011.623333
|View full text |Cite
|
Sign up to set email alerts
|

My Student Body: Effects of an Internet-Based Prevention Program to Decrease Obesity Among College Students

Abstract: The MSB-Nutrition program was effective in changing students' nutrition behaviors but had no effect on physical activity behaviors or weight loss. Suggestions for improving Internet-based interventions aimed at decreasing obesity rates among college students are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 21 publications
0
87
0
Order By: Relevance
“…Online stress management interventions aim to manage stress as well as other psychopathological issues [45] such as anxiety [68,69], prevention of obesity [70] and psychological distress [71]. In our literature review, according to a meta-analysis conducted in 2016 [45], only six studies had stress management as their principal goal [4649,72], and only three of these studies were carried out with university students [45,46,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Online stress management interventions aim to manage stress as well as other psychopathological issues [45] such as anxiety [68,69], prevention of obesity [70] and psychological distress [71]. In our literature review, according to a meta-analysis conducted in 2016 [45], only six studies had stress management as their principal goal [4649,72], and only three of these studies were carried out with university students [45,46,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the inform a tion avail able, 10 studies were considered to have low risk of bias (Chen et al , 2010(Chen et al , , 2011Gow et al , 2010;Kennedy et al , 2009;Kim et al , 2010;LaChausse, 2012;Luszczynska and Haynes, 2009;Østbye et al , 2012;Rosenkranz et al , 2010;Zask et al , 2012), nine had moder ate risk (Bayer et al , 2009;De Bock et al , 2012;Gentile et al , 2009;Gephart and Loman, 2013;Haire-Joshu et al , 2008;Hoffman et al , 2011;NeumarkSztainer et al , 2009;Siegel et al , 2010;van Wier et al , 2009), and six had high risk (Branscum et al , 2013;Foster et al , 2008;French et al , 2010;Spiegel and Foulk, 2006;Taylor et al , 2007;Warren et al , 2003). Nine studies repor ted random iz a tion by a computer, random number tables, or permuted blocks.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Nineteen of 25 studies repor ted posit ive effects on increas ing fruit and/or veget able consump tion (Bayer et al , 2009;Branscum et al , 2013;Chen et al , 2010Chen et al , , 2011De Bock et al , 2012;French et al , 2010;Gentile et al , 2009;Gephart and Loman, 2013;Haire-Joshu et al , 2008;Hoffman et al , 2011;Kennedy et al , 2009;Kim et al , 2010;LaChausse, 2012;Luszczynska and Haynes, 2009;Østbye et al , 2012;Spiegel and Foulk, 2006;Taylor et al , 2007;Warren et al , 2003;Zask et al , 2012), while five revealed no FV effects (Gow et al , 2010;Neumark-Sztainer et al , 2009;Rosenkranz et al , 2010;Siegel et al , 2010;van Wier et al , 2009). One study detected decreased FV consump tion (Foster et al , 2008).…”
Section: Effects On Fv Consump Tionmentioning
confidence: 99%
See 2 more Smart Citations